Le elezioni parlamentari in Ucraina: il partito “Servitore del Popolo” del Presidente Zelensky ottiene la maggioranza assoluta dei seggi e dà vita ad un governo maggioritario (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
For the first time since its independence, in Ukraine a single party, the Servant of the People (SdP) of President Zelensky, has managed to obtain the absolute majority in Parliament. Although this enables the SdP to form the government, external support will still be needed to approve the reforms proposed during the electoral campaign.
Keywords: Ukraine; Parliamentary elections; Zelensky; Hončaruk